A Relationship between Epithelial Maturation, Bronchopulmonary Dysplasia, and Chronic Obstructive Pulmonary Disease - Abraham B. Roos; Tove Berg; Magnus Nord (Pulmonary Medicine)
Premature infants frequently develop bronchopulmonary dysplasia (BPD). Lung immaturity and impaired epithelial differentiation contribute together with invasive oxygen treatment to BPD onset and disease progression. Substantial evidence suggests that prematurity is associated with long term pulmonary consequences. Moreover, there is increasing concern that lung immaturity at birth may increase the risk of developing chronic obstructive pulmonary disease (COPD). The mechanisms contributing to this phenomenon remains unknown, largely as a consequence of inadequate experimental models and clinical follow-up studies. Recent evidence suggests that defective transcriptional regulation of epithelial differentiation and maturation may contribute to BPD pathogenesis as well as early onset of COPD. The transcriptional regulators CCAAT/enhancer-binding protein (C/EBP)α and C/EBPβ, SMAD family member (Smad)3, GATA binding protein (GATA)6, and NK2 homeobox (NKX)2-1 are reported to be involved in processes contributing to pathogenesis of both BPD and COPD. Increased knowledge of the mechanisms contributing to early onset COPD among BPD survivors could translate into improved treatment strategies and reduced frequency of respiratory disorders among adult survivors of BPD. In this paper, we introduce critical transcriptional regulators in epithelial differentiation and summarize the current knowledge on the contribution of impaired epithelial maturation to the pathogenesis of inflammatory lung disorders.